Timing of complementary feeding and the risk of atopic eczema. (3rd December 2013) - Niinivirta, Katri; Isolauri, Erika; Nermes, Merja; Laitinen, Kirsi
Abstract Aim To find out whether there was an association between when complementary feeding was introduced and the appearance of atopic eczema in children with a family history of allergy. Methods This prospective study followed 256 mother and child pairs until the child was four‐years‐old. Repeated skin prick testing was performed and a clinical diagnosis of eczema made by a physician. The mothers kept a continuous diary about the introduction of complementary feeding. To control the possible reverse causation of delaying complementary food introduction due to presumed child allergy, parental suspicions of allergic reactions were recorded. Results The introduction of cereals and fish after seven‐months‐of‐age was associated with an increased risk of atopic eczema. However, when the parents' suspicions that their child might be exhibiting symptoms of allergic disease were taken into account, this effect was no longer significant. Conclusion We found no evidence that the timing of the introduction of complementary feeding increased the risk of atopic eczema in a high‐risk cohort, when parental suspicions were taken into account. Therefore, it seems that families with a history of allergy can safely comply with current feeding recommendations, although confirmation in further studies is warranted.